2015
DOI: 10.1039/c5ay01709b
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of high performance liquid chromatographic and derivative spectrophotometric methods for determination of gadodiamide in liposomal formulations

Abstract: High performance liquid chromatography and derivative spectrophotometry were applied for determination of gadodiamide in liposomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…20,[25][26][27][28][29] Despite the indisputable detectability provided by MS, the high cost of analysis and instrumentation justifies the development of simpler and less costly method. In a previous study by our research group, 2 an analytical method for the determination of Gd-DTPA-BMA by RP-LC/DAD was developed and validated. It showed to be linear in the range between 100 and 500 nmol mL -1 .…”
Section: Methods Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…20,[25][26][27][28][29] Despite the indisputable detectability provided by MS, the high cost of analysis and instrumentation justifies the development of simpler and less costly method. In a previous study by our research group, 2 an analytical method for the determination of Gd-DTPA-BMA by RP-LC/DAD was developed and validated. It showed to be linear in the range between 100 and 500 nmol mL -1 .…”
Section: Methods Validationmentioning
confidence: 99%
“…Despite this, its administration is contraindicated in patients presenting chronic renal failure due to the risk of developing nephrogenic systemic fibrosis. [1][2][3] Recently, the European Medicines Agency (EMA) 4 confirmed a review that found that Gd deposition can occur in brain tissues after the use of Gd contrast agents. Until the present date, there is no evidence that Gd deposition in the brain has caused any harm to patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atsriku et al (2002) and Campbell et al (2004) described the determination and identification of DIZE and its degradation products by liquid chromatography coupled with mass spectrometry (LC-MS). However, these methods are not suitable for 4-AD quantification, require complex instrumentation, and are more expensive than high performance liquid chromatography (HPLC) (Maia et al, 2015). Hence, the development of an analytical method is necessary to detect and identify 4-AD in pharmaceutical forms.…”
Section: Introductionmentioning
confidence: 99%